2010
DOI: 10.1097/ico.0b013e3181d927b9
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Subconjunctival Ranibizumab on Primary Pterygium: A Pilot Study

Abstract: Subconjunctival ranibizumab at a single dose of 0.3 mg was not associated with any side effects but had no effect on the extent of vascularization of primary pterygium in our study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
21
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 28 publications
0
21
0
Order By: Relevance
“…In a study of subconjunctival bevacizumab injection in corneal neovascularisation secondary to different aetiologies (ie, herpetic keratitis, chemical burn, failed graft), subconjunctival bevacizumab was found to be well tolerated and associated with a partial regression of corneal neovascularisation 21. However, the therapeutic response of pterygium to the antiangiogenesis drug ranibizumab has been inconsistent 11 12. Our present study demonstrated significantly higher tube formation by PECs with the C/C genotype than by cells with the C/T and T/T genotypes (figure 1C).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study of subconjunctival bevacizumab injection in corneal neovascularisation secondary to different aetiologies (ie, herpetic keratitis, chemical burn, failed graft), subconjunctival bevacizumab was found to be well tolerated and associated with a partial regression of corneal neovascularisation 21. However, the therapeutic response of pterygium to the antiangiogenesis drug ranibizumab has been inconsistent 11 12. Our present study demonstrated significantly higher tube formation by PECs with the C/C genotype than by cells with the C/T and T/T genotypes (figure 1C).…”
Section: Discussionmentioning
confidence: 99%
“…However, the therapeutic response of pterygium to the antiangiogenesis drug ranibizumab has been inconsistent. For example, Mandalos et al 11 showed that ranibizumab had no effect on the extent of vascularisation of primary pterygium while Shenasi et al 12 indicated that subconjunctival injection of bevacizumab immediately after surgical excision of a primary pterygium was well tolerated but did not significantly prevent recurrence of this condition.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from the analysis of conjunctival hyperemia there are a lot of applications in ophthalmology and other specializations in medicine using such techniques. In ophthalmology, digital photography and analysis are used for diagnosis of the anterior eye segment [37], for vessel detection in corneal transplants [38], for analyzing the corneal involvement of pterygium conjunctivae [39,40], for noninvasive calculation of hemoglobin in the wide field of emergency medicine [41], for examining rotational stability of intraocular lenses [42], in diagnosis of dry eye [43] and in the observation of side effects of antiglaucomatous treatment [44]. In dermatology they are implemented for measuring erythema and edema of the skin prick test [45,46,47] or intradermal skin tests [48], for analyzing repigmentation during treatment of vitiligo [49], for quantification of skin lesions [50], and in diagnosis and treatment of atopic dermatitis [51,52].…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] The role of anti-VEGF therapy in the treatment of primary or recurrent pterygium is evaluated in several studies. 12,15,[22][23][24][25][26] In these studies, it has been postulated that anti-VEGF therapy can inhibit limbal-conjunctival neovascularization and induce regression of the fibrovascular proliferation in the pterygium tissue. Bevacizumab is an anti-VEGF agent and has been used widely in ophthalmology practice to treat the abnormal vascular conditions of the choroid, retina, and cornea.…”
Section: Discussionmentioning
confidence: 99%
“…21 The effects of topical or subconjunctival bevacizumab on primary or recurrent pterygium have been evaluated in several studies, and successful outcomes have been achieved. [22][23][24][25][26] This study aimed to demonstrate the amount of the regression of the pterygium tissue quantitatively after intralesional bevacizumab administration in patients with primary pterygium. For this purpose, Pentacam Comprehensive Eye Scanner (Pentacam CES; Oculus GmbH, Wetzlar, Germany) was used.…”
mentioning
confidence: 99%